2021
DOI: 10.1029/2020ja028852
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal and Rock in Space: Cluster RAPID Observations of Fe and Si

Abstract: Knowledge about composition of matter in space is important for assessing formation and evolution of planets and their habitability. Heavy ions and molecular ions are also trace particles and can provide information about transport of matter through space and across boundaries. Identifying the source and supply routes of matter tells us about redistribution and migration of matter through space into the planetary and cometary system for short time scales and about planetary formation and evolution on geologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
(172 reference statements)
0
2
0
Order By: Relevance
“…Additionally, understanding the sources, energization mechanisms, and the overall dynamics of molecular ions in the magnetosphere-ionosphere system could possibly help understand the impact of the minor heavy ion species in the magnetosphere. Cluster (Haaland et al, 2021) and Geotail (Christon et al, 2017) missions have reported the observations of metal ions in the magnetosphere, but the sources and the transport mechanisms of these metal ions are still largely unknown. This review paper is intended to help inform and guide future ionosphere and magnetosphere studies, and provides context for the available observations of molecular ions.…”
Section: Missionmentioning
confidence: 99%
“…Additionally, understanding the sources, energization mechanisms, and the overall dynamics of molecular ions in the magnetosphere-ionosphere system could possibly help understand the impact of the minor heavy ion species in the magnetosphere. Cluster (Haaland et al, 2021) and Geotail (Christon et al, 2017) missions have reported the observations of metal ions in the magnetosphere, but the sources and the transport mechanisms of these metal ions are still largely unknown. This review paper is intended to help inform and guide future ionosphere and magnetosphere studies, and provides context for the available observations of molecular ions.…”
Section: Missionmentioning
confidence: 99%
“… Number of events showing Fe+ ions detected by Cluster from 2001 to 2019 (from Haaland et al., 2019). The F10.7 index is shown as a black line.…”
Section: Science Highlightsmentioning
confidence: 99%